Elimination of ceftiofur hydrochloride residue in postpartum cows' milk after intramammary infusing at dry-off - Ji-jun KANG; Yi-ming LIU; Lei-lei ZHAO; Fei XU; Xiao-jie CHEN; Xing YAN; Xiu-bo LI (Journal of Integrative Agriculture, 2018)
The purpose of this study was to investigate the residue elimination of ceftiofur hydrochloride in milk of postpartum cows after intramammary infusing at dry-off. An ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was developed and validated to detect ceftiofur hydrochloride residue in milk. Through preprocessing, ceftiofur hydrochloride was derivatized into a more stable compound dedfuroyl ceftiofur acetamide (DCA) for further analysis. The linear range of DCA was 0.1 to 50 μg kg−1. Average recoveries of DCA were 82.52–105.86%. The intra-day and interday coefficients of variation (CV) were 2.95–9.82 and 6.41–7.43%, respectively. The limit of detection (LOD) and limit of quantitation (LOQ) scores were 0.05 and 0.1 μg kg−1, respectively. These parameters showed this method was reliable and valid. Twelve cows were administrated 10 mL ceftiofur hydrochloride by intramammary infusion (corresponding to 500 mg ceftiofur) to each udder after the last milking before the dry-off period. Milk was collected from each udder of cow at 12, 24, 36, 48, 60 and 72 h after calving and was mixed for each time point and each cow, then subjected to UPLC-MS/MS analysis. The results showed, the DCA concentrations in all milk samples were less than LOQ and the maximum residue limit (MRL) 100 μg kg−1, which suggested the withdrawal time of ceftiofur hydrochloride intramammary infusion used for preventing and curing mastitis in dry cows was 0 day. The study provided guidance for the clinical applications of ceftiofur hydrochloride intramammary infusion (dry cow).